Chinese poetry and translation : rights and wrongs - Crevel, Maghiel van; Klein, Lucas (Amsterdam University Press, 2019)
Chinese Poetry and Translation: Rights and Wrongs' offers fifteen essays on the triptych of poetry + translation + Chinese. The collection has three parts: "The Translator's Take," "Theoretics," and "Impact." The conversation stretches from queer-feminist engagement with China's newest poetry to philosophical and philological reflections on its oldest, and from Tang- and Song-dynasty classical poetry in Western languages to Baudelaire and Celan in Chinese. Translation is taken as an interlingual and intercultural act, and the essays foreground theoretical expositions and the practice of translation in equal but not opposite measure. Poetry has a transforming yet ever-acute relevance in Chinese culture, and this makes it a good entry point for studying Chinese-foreign encounters. Pushing past oppositions that still too often restrict discussions of translation-form versus content, elegance versus accuracy, and "the original" versus "the translated"--This volume brings a wealth of new thinking to the interrelationships between poetry, translation, and China